2021
DOI: 10.1108/ejm-06-2019-0448
|View full text |Cite
|
Sign up to set email alerts
|

Thank you but no thank you: the impact of negative moral emotions on customer responses to preferential treatment

Abstract: Purpose Although preferential treatment has been considered a positive relationship marketing tactic, this research aims to examine how perceived harm to others as a result of preferential treatment invokes consumers’ negative moral emotions and negative attitudes towards the service provider. Design/methodology/approach Four studies are presented in this research. A pilot study first provides empirical evidence that customers who receive preferential treatment are aware of potential harm caused to other cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…These research findings contribute to the growing literature on preferential treatment, moral emotions and the need for distinction. Although we are not the first researchers to demonstrate that preferential treatment may have negative outcomes (Jiang et al, 2013;Palmeira et al, 2016;Pontes et al, 2021), this is the first research showing that the effect of perceived harm to others on customers attitudes towards the service provider is moderated by the individual need for distinction and mediated by negative moral emotions, such that an effect is found for those with a low need for distinction but not for those with a high need for distinction. Previous research has identified that there are negative outcomes of preferential treatment in matters concerning the self.…”
Section: Theoretical Contributionsmentioning
confidence: 72%
See 2 more Smart Citations
“…These research findings contribute to the growing literature on preferential treatment, moral emotions and the need for distinction. Although we are not the first researchers to demonstrate that preferential treatment may have negative outcomes (Jiang et al, 2013;Palmeira et al, 2016;Pontes et al, 2021), this is the first research showing that the effect of perceived harm to others on customers attitudes towards the service provider is moderated by the individual need for distinction and mediated by negative moral emotions, such that an effect is found for those with a low need for distinction but not for those with a high need for distinction. Previous research has identified that there are negative outcomes of preferential treatment in matters concerning the self.…”
Section: Theoretical Contributionsmentioning
confidence: 72%
“…Preferential treatment is often lauded for generating positive emotional and behavioural responses from customers who receive special benefits; however, emerging research calls into question the effectiveness of preferential treatment as a relationship marketing strategy by investigating its negative effects (Henderson et al , 2011; Jiang et al , 2013; Lacey et al , 2007; Palmeira et al , 2016; Pontes et al , 2021; Reinartz and Kumar, 2002; Wagner et al , 2009) . Research shows that advantaged customers may feel embarrassed when preferentially treated in the presence of other customers (Butori and De Bruyn, 2013, Pontes et al , 2021) or experience concerns about negative judgment and retaliation from others, which leads to social discomfort and reduced satisfaction (Jiang et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in the study were awarded a small monetary incentive (US$0.85). To ensure the quality of the panel data, the recruitment techniques were in line with best practices (Kees et al , 2017) and with past research on MTurk (Pontes et al , 2021; Pontes and Pontes, 2021; Pontes and Hoegg, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…While embarrassment was traditionally viewed as a self‐conscious emotion that requires the presence of others (Miller & Tangney, 1994; Tangney et al, 1996), it can also be experienced privately (private embarrassment) (Krishna et al, 2019), vicariously (Kilian et al, 2018), and in the presence of technology (Tsai et al, 2021), though technology may reduce embarrassment in comparison (Pitardi et al, 2021). Though some recent studies suggest that there may be some positive outcomes to embarrassment in some contexts (Herter et al, 2021; Tsai et al, 2021), the majority of the literature suggests that consumers strive to avoid embarrassment (Blair & Roese, 2013; Nichols et al, 2015; Pontes et al, 2021). While embarrassment has been studied in terms of how advertising may embarrass the consumer (Agarwal et al, 2013), the influence of perceptions of product embarrassment on the relationship between product message appeals and excitement has yet to be explored.…”
Section: Literature Reviewmentioning
confidence: 99%